2005
DOI: 10.1084/jem.20042081
|View full text |Cite
|
Sign up to set email alerts
|

IκB kinase (IKK)β, but not IKKα, is a critical mediator of osteoclast survival and is required for inflammation-induced bone loss

Abstract: Transcription factor, nuclear factor κB (NF-κB), is required for osteoclast formation in vivo and mice lacking both of the NF-κB p50 and p52 proteins are osteopetrotic. Here we address the relative roles of the two catalytic subunits of the IκB kinase (IKK) complex that mediate NF-κB activation, IKKα and IKKβ, in osteoclast formation and inflammation-induced bone loss. Our findings point out the importance of the IKKβ subunit as a transducer of signals from receptor activator of NF-κB (RANK) to NF-κB. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
241
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(257 citation statements)
references
References 54 publications
12
241
0
1
Order By: Relevance
“…Based on these data, both positive and negative regulators appear to be less dispensable in mature cells where they may establish a balance that controls the activity of NF-B. NF-B has been shown to protect osteoclast progenitors from apoptosis (26) and to be activated in bone marrow and cord blood progenitor cells (27). Additionally, it has been described that NF-B activation can prevent chondrogenesis and myogenesis from mesenchymal cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, both positive and negative regulators appear to be less dispensable in mature cells where they may establish a balance that controls the activity of NF-B. NF-B has been shown to protect osteoclast progenitors from apoptosis (26) and to be activated in bone marrow and cord blood progenitor cells (27). Additionally, it has been described that NF-B activation can prevent chondrogenesis and myogenesis from mesenchymal cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the capacity of NF-kB to inhibit or promote apoptosis, loss of IKKb function has similar outcomes, which depend on the type of stress and the tissue involved (Graham and Gibson, 2005). For example, whereas conditional knockouts have shown that IKKb protects macrophages , osteoclasts (Ruocco et al, 2005) and gut epithelium (Chen et al, 2003) from apoptosis triggered by TLR signals, IKKb is required for neuronal apoptosis induced by ischemic brain injury (Herrmann et al, 2005). While a detailed account of the role played by IKKb in cell survival is dealt with elsewhere in this edition (Ge´linas, 2006), the specific ablation of IKKb in hepatocytes helps illustrate the nuances of NF-kB antiapoptotic function in adult mice.…”
Section: Ikkbmentioning
confidence: 99%
“…For example, IKKb is crucial for the production of various inflammatory cytokines by macrophages , it is involved in inflammation-induced bone loss (Ruocco et al, 2005) and it has been implicated in the inflammatory component of obesityinduced insulin resistance (Arkan et al, 2005). In the case of the link between inflammation and obesityinduced diabetes, conditional deletion of IKKb in different mouse tissues reveals the importance of NF-kBdependent myeloid inflammatory responses in this disease (Arkan et al, 2005).…”
Section: Ikkbmentioning
confidence: 99%
“…Bone remodeling depends on the orchestrated balance between bone formation and bone resorption. The role for IKK-NF-κB signaling in osteoclastogenesis is well established, 16 but far less is known about role for IKKβ in bone formation. We therefore crossed Ikkβ F/F mice 10 with mice expressing Cre recombinase under the control of type I collagen promoter elements.…”
Section: Resultsmentioning
confidence: 99%
“…The development and activation of osteoclasts are well characterized at the genetic and molecular levels, 14,15 and the role of IKK signaling in these processes has been established. 16 In contrast, less is known about the role of IKK in osteoblast development.…”
mentioning
confidence: 99%